A multi‐center phase Ib study of oxaliplatin (NSC#266046) in combination with fluorouracil and leucovorin in pediatric patients with advanced solid tumors1. Issue 2 (28th September 2012) - Macy, Margaret E.; Duncan, Tracey; Whitlock, James; Hunger, Stephen P.; Boklan, Jessica; Narendren, Aru; Herzog, Cynthia; Arceci, Robert J.; Bagatell, Rochelle; Trippett, Tanya; Christians, Uwe; Rolla, Katherine; et al.
Abstract Background Platinum agents have been used for a variety of cancers, including pivotal use in pediatric tumors for many years. Oxaliplatin, a third generation platinum, has a different side effect profile and may provide improved activity in pediatric cancers. Procedure Patients 21 years or younger with progressive or refractory malignant solid tumors, including tumors of the central nervous system were enrolled on this multi‐center open label, non‐randomized Phase 1 dose escalation study. The study used a standard 3 + 3 dose escalation design with 2 dose levels (85 and 100 mg/m2) with an expansion cohort of 15 additional patients at the recommended dose. Patients received oxaliplatin at the assigned dose level and 5‐fluorouracil (5‐FU) bolus 400 mg/m2 followed by a 46‐hour 5‐FU infusion of 2, 400 mg/m2 every 14 days. The leucovorin dose was fixed at 400 mg/m2 for all cohorts. Results Thirty‐one evaluable patients were enrolled, 8 at 85 mg/m2 and 23 at 100 mg/m2 for a total of 121 courses. The median age was 12 years (range 2–19 years). The main toxicities were hematologic, primarily neutrophils and platelets. The most common non‐hematologic toxicities were gastrointestinal. Stable disease was noted in 11 patients (54% of evaluable patients) and 1 confirmed partial response in a patient with osteosarcoma. Conclusions The maximum planned dose of oxaliplatin at 100 mg/m2 per dose in combination with 5‐FU and leucovorin was safe and well tolerated and in this patient population. This combination demonstrated modest activity in patients with refractory or relapsed solid tumor and warrants further study. Pediatr Blood Cancer 2013;60:230–236. © 2012 Wiley Periodicals, Inc.